The Impact of Corruption and Money Laundering on Foreign Direct Investment in ASEAN - Nugraha, I Wayan Yasa (Jurnal Ekonomi Kuantitatif Terapan; 2013: Vol. 6, No. 2, Agustus 2013 (pp. 71-143), 2013)
The purpose of this study is to examine the impact of corruption and money laundering on Foreign Direct Investment (FDI) inflow in ASEAN by using panel data which covers ten years observation (2000–2009) and five cross sections of selected countries i.e. Indonesia, Malaysia, Singapore, Thailand, and Philippines. The model is estimated using ordinary least square method with fixed effect estimation. The result shows that there is a significant positive association between the establishment of Financial Intelligence Unit (FIU) and FDI inflow, while Corruption Perception Index (CPI), as the proxy of corruption, does not significantly affect FDI inflow.
Keywords: corruption; money laundering; FDI; panel data analysis